A gestão das unidades de atenção básica em saúde em um município paulista: concepções dos enfermeiros sobre o trabalho gerencial - Schiavetto, Lucele (2013)
This work permeates discussions about the management in primary care, it is a topic of high complexity, while the unique and undeniable importance. At the time of reorientation of care model allows the study and management understand how the work process is occurring in everyday life, and thus analyze the performance of nurses' actions in Primary relationship management, revealing strengths and difficulties in the process of transforming health practices. Manage Health in order to optimize it, especially the Basic Units, it requires a critical analysis of nurses for decision making and the development of reflective thinking. Therefore, this study aimed to analyze the work of the nurse manager of teams of primary health care; know the actions undertaken identifying factors that enhance and hinder the achievement of these actions in the Basic Health Unit; identify the relationship of nursing education and its role as unit manager, and identify the nurse's conception of its role in management. This is a case study in which data collection was used documentary analysis of the health plan, the structured interview and the completion of the focus group, and then the thematic analysis of the data, the study site was a city of São Paulo and 12 nurses participated in the survey of Primary Care Units. The results demonstrate the managers s profile as well as their management actions characterized in categories: Acting as nurse management and care; Relationship training with their performance management unit; Importance of planning for management; Factors that enhance and hinder the realization of shares management. Revealing the profile of nurse managers, as all units are managed by Primary Care nurses in most women with an average age between 35 and 54 years, most with graduate students and those with masters or specialization in the area are not management, the large number of nurses are in charge of more than 5 years, and contatração process occurs through the public tender for the Basic Health Units (BHU) and selection process for the Family Health Program (FHP). Respondents refer exercise beyond management function, care activities, since the units of Primary Care from the municipality has only one nurse in the unit, and state become overloaded, failing to perform their duties properly, hindering planning management unit. It also points to the lack of staff meeting, not recognizing this tool as a facilitator in the process of management. It also demonstrates that the degree contributes very little to the financial management and claim that experience is more important and not using planning as a management tool. Thus, it is important to note that this survey revealed a work process permeated by situations that characterize a fragmented management process, centralized in a single member of staff, the nurses, the absence of effective teamwork with horizontalizadas relations and deficiency qualified human resource.